The Effect of Resistance Band Training on Arm Muscle Strength Endurance of Basketball Players - Tubagus Muhammad Fenter Mulya; Alen Rismayadi; Yopi Kusdinar; Mulyana (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of resistance band training on increasing the endurance of arm muscle strength in adolescent basketball players. The method used is an experiment with a pre-test and post-test design in one group. The subjects of the study consisted of extracurricular basketball players who followed a training program for six weeks (12 sessions). The instrument used to measure arm muscle strength was a 60-second push-up test. The results of the statistical analysis showed a significant increase in the average value, from 20.20 (pre-test) to 25.00 (post-test). This finding is supported by previous studies stating that resistance band-based training is effective in increasing muscle strength, even in the elderly group. In addition to increasing strength, the advantages of resistance bands lie in their flexibility, portability, and high level of safety, making them suitable for use by school-age athletes. Thus, resistance band training can be an efficient and effective alternative in the youth basketball physical development program, especially in increasing arm muscle endurance to support the performance of basic game techniques.